2012
DOI: 10.7888/juoeh.34.363
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Characteristics of a Real-time Monitor Using a Photoionization Detector on Organic Solvent Vapors

Abstract: : Measurements of organic solvents in the work environment are carried out by either direct sampling using plastic bags/gas chromatography, solid sorbent adsorption using charcoal tubes/gas chromatography, or by a direct reading method using detector tubes. However, these methods cannot always measure the work environment accurately because the concentration of hazardous materials changes from time to time, and from space to space. In this study, the sensor characteristics of a real time monitor using a photoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Therefore, it is reasonable that methanol, which could not be detected by the other two monitors, can be detected by this monitor with a linear response. In addition to semiconductor sensors, we also previously confirmed that the PID sensor also exhibited temporary deterioration when we used another monitor 4) . Therefore, when we use such real-time monitors for determination of organic vapors, calibration should be conduct- ed in advance of measurement.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, it is reasonable that methanol, which could not be detected by the other two monitors, can be detected by this monitor with a linear response. In addition to semiconductor sensors, we also previously confirmed that the PID sensor also exhibited temporary deterioration when we used another monitor 4) . Therefore, when we use such real-time monitors for determination of organic vapors, calibration should be conduct- ed in advance of measurement.…”
Section: Discussionsupporting
confidence: 69%
“…We have been studying the sensor characteristics of several real-time monitors for organic vapors or volatile organic compounds 3−6) . First, we tested a monitor with a photo ionization detector (PID) 4) for 52 organic solvents. Although this monitor had high sensitivity and a linear response was obtained for many solvents, it showed low or no response for some solvents with a high ionization potential.…”
mentioning
confidence: 99%
“…This feature is an advantage when developing a new gas detector. In addition, colorimetric gas detectors currently commercially available can measure more than 300 types of gases [80][81][82][83][84][85][86][87][88][89][90].…”
Section: Comparison Of Various Gas Detector Technologiesmentioning
confidence: 99%